Empathy in Early Adulthood: The Role of Big Five Personality Traits and Self-Compassion - Ahmad, Miqdad Daly; Nurmaulida, Diah Liandary; Maharani, Aulia; Najaa, Maysaroh Azmia Ummi; Abbas, A. Annisa Alifah; Assabil, Vibby Sawa; Pambudi, Fitrah Metta Rilo; Zenitha, Rizka Aulia; S., Mahardika Hizbullah A. (Psikoislamedia: Jurnal Psikologi, 2026)
Empathy is a crucial capacity in early adulthood, as it supports interpersonal relationships and mental health. This study examined the effects of Big Five personality traits and self-compassion on empathy, as well as differences in empathy by gender and age. A correlational design was employed with 207 participants aged 18–23 years who were recruited through convenience sampling. The instruments included the Big Five Personality Scale, the Self-Compassion Scale, and the Basic Empathy Scale. Data were analyzed using multiple linear regression, independent-samples t tests, and one-way ANOVA. The results showed that Big Five personality traits and self-compassion jointly predicted empathy. However, only agreeableness and neuroticism were significant individual predictors, whereas extraversion, conscientiousness, openness, and self-compassion were not statistically significant. Gender comparisons indicated that females scored higher than males on neuroticism and empathy. Age-group analyses revealed significant differences in agreeableness. These findings indicate that empathy in early adulthood is primarily shaped by interpersonal personality characteristics and emotional sensitivity, with gender playing a role, whereas age differences within this range are less influential.